Características maternas e fatores de risco para pré-eclâmpsia em gestantes - Eilen Tainá Matos Ferreira; Nádya dos Santos Moura; Maria Luziene de Sousa Gomes; Erielton Gomes da Silva; Maria das Graças da Silva Guerreiro; Mônica Oliveira Batista Oriá (Universidade Federal do Ceará, 2019)
Objective to investigate maternal characteristics and risk factors for development of preeclampsia in pregnant women.Methods documentary and retrospective study based on medical records of pregnant women of six Family Health Strategy teams. Information of 94 pregnant women was collected through a form and used in the study.Results the pregnant women were aged between 15 and 47 years. The risk factors for development of preeclampsia in the sample were primiparity 40 (42.6%), chronic hypertension 4 (4.3%), multiple pregnancy 9 (9.6%), diabetes mellitus and obesity 8 (8.6%), and age >40 years (1.1%).Conclusion there were some risk factors for the development of preeclampsia in the evaluated registries, such as primiparity, chronic hypertension, diabetes mellitus and obesity.